Step test and physical working capacity in female volleyball players: the paradox of better performance in the older athletes - Nikolaidis, P.T.; Afonso, J.; Knechtle, B.; Clemente-Suárez, V.J.; Torres-Luque, G. (Cuadernos de Psicología del Deporte, 2016)
The aim of the present study was to compare two popular submaximal tests of aerobic capacity, the YMCA step test and the physical working capacity at heart rate (HR) 170 bpm test (P170), in competitive female volleyball players. The participants (n = 152, age 12.78-41.67 yrs) were examined for anthropometric characteristics and performed the YMCA step test. Heart rate (HR) was recorded at the end of the test (Stepend) and at the end of the first minute of recovery (Steprec). P170 test was expressed in both absolute (P170,abs, W) and relative values (P170,rel, W.kg-1). In addition, a sub-group (n = 14) was tested again one year later. The YMCA step test correlated largely (Steprec) and very largely (Stepend) with P170,rel (r = –0.58 and r = –0.76, p < 0.001, (respectively), and P170,abs (r = –0.54 and r = –0.68, p < 0.001, respectively). No correlation was observed among percentage changes in the tests of aerobic capacity over a year (p>0.05). Age correlated low-to-moderately with all indices of aerobic capacity (0.23 ≤ │r│ ≤ 0.45, p<0.05), i.e. the older the age, the better the aerobic capacity. Based on the findings of the present study, it was concluded that the YMCA step test (especially the Stepend index) and P170 might be used interchangeably by coaches and trainers to monitor aerobic capacity of female volleyball players. The paradoxically increase of aerobic capacity with age should be attributed to the assessment methods which were based on HR and to the decrease of maximal HR